2011
DOI: 10.1103/physrevb.84.134418
|View full text |Cite
|
Sign up to set email alerts
|

Width of the longitudinal magnon in the vicinity of the O(3) quantum critical point

Abstract: We consider a three-dimensional quantum antiferromagnet in the vicinity of a quantum critical point separating the magnetically ordered and the magnetically disordered phases. A specific example is TlCuCl 3 where the quantum phase transition can be driven by hydrostatic pressure and/or by external magnetic field. As expected, two transverse and one longitudinal magnetic excitations have been observed in the pressure-driven magnetically ordered phase. According to the experimental data, the longitudinal magnon … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

7
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 28 publications
7
49
0
Order By: Relevance
“…3). Both findings establish the amplitude mode as a relatively broad, critically well-defined excitation on the bicube lattice, as observed also in experiments [17,18] on TlCuCl 3 and within field-theory calculations [4,21]. In summary, we provided robust evidence for the presence of multiplicative logarithmic corrections to the leading Gaussian mean-field scaling of the triplon excitation gap softening near the quantum critical point.…”
supporting
confidence: 59%
See 1 more Smart Citation
“…3). Both findings establish the amplitude mode as a relatively broad, critically well-defined excitation on the bicube lattice, as observed also in experiments [17,18] on TlCuCl 3 and within field-theory calculations [4,21]. In summary, we provided robust evidence for the presence of multiplicative logarithmic corrections to the leading Gaussian mean-field scaling of the triplon excitation gap softening near the quantum critical point.…”
supporting
confidence: 59%
“…In contrast to the situation in lower-dimensional systems, we observe in this three-dimensional coupled-dimer system a distinct signal from the amplitude mode also in the dynamical spin structure factor. The width of the Higgs mode resonance is observed to scale linearly with the Higgs mass near criticality, indicative of this critically well-defined excitation mode of the symmetry broken phase.Quantum critical three-dimensional antiferromagnets provide considerably valuable condensed matter realizations of (infrared) asymptotically free quantum field theories: based on the quantum-to-classical mapping, the critical field theory that describes the underlying quantum critical point is the classical four-dimensional O(3) φ 4 -theory [1][2][3][4][5][6]. Due to a logarithmic decay of the renormalized interaction strength upon approaching the critical point, this field theory exhibits logarithmic corrections to a Gaussian fixed point [7][8][9][10].…”
mentioning
confidence: 99%
“…In this case the mass squared term in the magnon Lagrangian changes sign at the transition [20]. Now we consider a similar QPT for spinons described by the Lagrangian (1), m 2 ∝ g − g c .…”
mentioning
confidence: 99%
“…Recently a new universal behavior between the thermal and quantum properties of (3+1)-dimensional dimerized quantum antiferromagnets has been established [14,15]. Specifically, using the relevant field theory, it is shown that the Néel temperature T N can be related to the staggered magnetization density M s near a quantum critical point (QCP).…”
mentioning
confidence: 99%